Work Optimization Predicts Accretionary Faulting: An Integration of Physical and Numerical Experiments. Issue 9 (25th September 2017) - McBeck, Jessica A.; Cooke, Michele L.; Herbert, Justin W.; Maillot, Bertrand; Souloumiac, Pauline
Abstract: We employ work optimization to predict the geometry of frontal thrusts at two stages of an evolving physical accretion experiment. Faults that produce the largest gains in efficiency, or change in external work per new fault area, Δ W ext /Δ A, are considered most likely to develop. The predicted thrust geometry matches within 1 mm of the observed position and within a few degrees of the observed fault dip, for both the first forethrust and backthrust when the observed forethrust is active. The positions of the second backthrust and forethrust that produce >90% of the maximum Δ W ext / Δ A also overlap the observed thrusts. The work optimal fault dips are within a few degrees of the fault dips that maximize the average Coulomb stress. Slip gradients along the detachment produce local elevated shear stresses and high strain energy density regions that promote thrust initiation near the detachment. The mechanical efficiency ( W ext ) of the system decreases at each of the two simulated stages of faulting and resembles the evolution of experimental force. The higher Δ W ext /Δ A due to the development of the first pair relative to the second pair indicates that the development of new thrusts may lead to diminishing efficiency gains as the wedge evolves. The numerical estimates of work consumed by fault propagation overlap the range calculated from experimental force data and crustal faults. The integration of numerical and physical experiments provides a powerful approach that demonstrates the utility of work optimization to predict the development of faults. Key Points: We compare numerical and physical experiments Work optimization prediction closely matches observed Work optimization predicts faulting more exactly than max Coulomb stress Plain Language Summary: This contribution synthesizes results from physical analog accretion experiments and numerical simulations in order to predict the evolution of frontal thrusting within accretionary systems. We employ a novel method of predicting accretion thrust geometry with work optimization, and compare these predictions to thrust geometries observed in the physical accretion experiment as well as to the predictions of Coulomb shear stress. The new work optimization approach successfully predicts the observed geometry of thrusts in the two investigated stages of accretionary faulting.